Phosphine/diimine ruthenium complexes with Cl−, CO, NO+, NO2−, NO3− and pyridine ligands: Pro-apoptotic activity on triple-negative breast cancer cells and DNA/HSA interactions. (1st April 2018) - Silva, Henrique Vieira Reis; Dias, Júlia Scaff Moreira; Ferreira-Silva, Guilherme Álvaro; Vegas, Legna Colina; Ionta, Marisa; Corrêa, Charlane Cimini; Batista, Alzir Azevedo; Barbosa, Marília Imaculada Frazão; Doriguetto, Antônio Carlos
Graphical abstract: Four phosphine/diimine ruthenium complexes with general formula [RuCl(L)(dppb)(4, 4′-Mebipy)](PF6 ) n (L = CO, NO +, NO2 − or pyridine) and one with formula [Ru(NO3 )(dppb)(4, 4′-Mebipy)]PF6 were obtained. The complex containing the pyridine ligand displays cytotoxic activity/selectivity. Also demonstrated pro-apoptotic activity on MDA-MB-231 as well as its ability to reduce colony formation. Abstract: A series of five new ruthenium phosphine/diimine complexes were prepared and characterized by IR, UV–Vis, 1 H, 31 P{ 1 H} and 13 C{ 1 H} NMR spectroscopies, elemental analyses and cyclic voltammetry. Four of the complexes have the general formula ct-[RuCl(L)(dppb)(4, 4′-Mebipy)](PF6 ) n (dppb = 1, 4-bis(diphenylphosphino)butane, 4, 4′-Mebipy = 4, 4′-dimethyl-2, 2-bipyridine and L = CO, NO +, NO2 − or pyridine), and one has the formula [Ru(NO3 )(dppb)(4, 4′-Mebipy)]PF6, where NO3 − is a bidentate ligand. In addition, the crystal structure of the complex ct- [RuCl(CO)(dppb)(4, 4′-Mebipy)]PF6 was elucidated by single-crystal X-ray diffraction analysis, which supported the geometry of the compounds suggested by the 31 P NMR experiments. The cytotoxic activity of the synthesized compounds was evaluated against five cancer cell lines: HepG2 (liver), HT144 (melanoma), A549 (lung), MDA-MB-231 (breast) and HCT-9 (colon). Human serum albumin (HSA) and DNA binding experiments were also conducted. The HSA binding constants and thermodynamic parameters suggested spontaneous interactions of the complexes with this protein through van der Waals forces and hydrogen bonding. A spectroscopic titration study indicated that the compounds interacted with ct-DNA, exhibiting binding constants, K b, on the order of 1.0 × 10 4  M −1 . Additionally, the ruthenium complex containing pyridine displayed cytotoxic activity against HT144, A549, and MDA-MB-231. In addition, it demonstrated pro-apoptotic activity on MDA-MB-231 cells as well as the ability to reduce colony formation. These findings are very promising and have motivated further studies for identifying the molecular target underlying the antitumor activity of the ruthenium(II)/pyridine complex against triple-negative breast cancer.